p53 Binding Protein 53BP1 Is Required for DNA Damage Responses and Tumor Suppression in Mice - Ward, Irene M. (American Society for Microbiology, 2003)
53BP1 is a p53 binding protein of unknown function that binds to the central DNA-binding domain of p53. It relocates to the sites of DNA strand breaks in response to DNA damage and is a putative substrate of the ataxia telangiectasia-mutated (ATM) kinase. To study the biological role of 53BP1, we disrupted the 53BP1 gene in the mouse. We show that, similar to ATM(−/−) mice, 53BP1-deficient mice were growth retarded, immune deficient, radiation sensitive, and cancer prone. 53BP1(−/−) cells show a slight S-phase checkpoint defect and prolonged G(2)/M arrest after treatment with ionizing radiation. Moreover, 53BP1(−/−) cells feature a defective DNA damage response with impaired Chk2 activation. These data indicate that 53BP1 acts downstream of ATM and upstream of Chk2 in the DNA damage response pathway and is involved in tumor suppression.